Preoperative single dose versus conventional antibiotic prophylaxis in thyroid surgery - Islam, Mohammad Zahirul; Kamal, Mohammad Shah; Hafiz, Md Abdul; Hossan, Md Mosarraf; Islam, Md Saiful; Biswas, Supran (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Surgical Site Infection (SSI) is the most frequent type of Health care-associated infections (HAI) in low- and middle-income countries and affects up to one-third of patients who have undergone a surgical procedure. SSI incidence is the second most frequent type of HAI in Europe and the United States of America. Objective: This study aimed to compare the frequency of SSIs after thyroid surgeries with preoperative single dose antibiotic and conventional multi doses prophylaxis antibiotic regimens. Methods: This randomized clinical trial was carried out in the Department of Otolaryngology and Head Neck Surgery, Chittagong Medical College Hospital from January 2020 to March 2021. Eighty-four patients who underwent elective thyroid surgery were randomly assigned into two equal groups of 42 each. They received either a single dose preoperative injectable antibiotic or a conventional antibiotic regimen for seven days. Patients were followed up till the 30th post-operative day to assess postoperative SSI and other complications. Results: The majority of the patients were female (90%) and in the age group of 30 to 39 years (33%). Both groups were similar in terms of their demographic characteristics. The most common indication of the surgery was nodular goiter and most of the patients underwent hemithyroidectomy. The mean duration of operation was 120 minutes. No SSI or other major complications were observed in this study. Conclusion: Preoperative single-dose antibiotic is comparable to conventional multi-dose prophylaxis antibiotic regimens in elective thyroid surgery. J Bangladesh Coll Phys Surg 2024; 42: 247-252